THE USE OF SUBCISION IN CONJUNCTION WITH FRACTIONAL CARBON DIOXIDE LASER TO IMPROVE ATROPHIC ACNE SCARS - SHARMA, PRIYANKA; SINGH, AJIT; TRIPATHI, ADITYA KUMAR (International Journal of Current Pharmaceutical Research, 2024)
Objective: Acne is a prevalent skin condition affecting a wide range of age groups, often leading to severe scarring if left untreated. The use of subcision combined with fractional CO2 laser therapy has been posited as a potentially more effective treatment method for atrophic acne scars compared to standalone laser treatment. Methods: This clinical trial was conducted at Asha Derma Clinic, Gorakhpur, Uttar Pradesh, from 30th March 2023 to 30th March 2024. Thirty patients with ice pick and rolling-type atrophic acne scars were enrolled. Participants were treated on one side of their face with five sessions of fractional CO2 laser and on the other side with one session of subcision with fractional CO2 laser combined with four sessions of fractional CO2 laser alone. Outcomes were assessed through scar improvement and patient satisfaction at 1, 2, and 6 mo post-treatment, with data analysis performed using ANOVA and the Wilcoxon rank-sum test. Results: Significant improvements were observed in both recovery levels and patient satisfaction. The combined method showed higher recovery percentages (40-65%, Mean±SD: 54.7±7) compared to the laser alone (30-55%, Mean±SD: 43±11.1), with a p-value of 0.0005. Patient satisfaction also favored the combined method (1.8-3, Mean±SD: 6.6±1.2) over laser treatment alone (1.6-4, Mean±SD: 5.2±1.8), with a p-value of 0.0007. Conclusion: The study demonstrated that subcision combined with fractional CO2 laser therapy significantly enhances recovery levels and patient satisfaction in the treatment of atrophic acne scars, suggesting a robust advantage of integrating both treatments.